2013
DOI: 10.1002/jhm.2087
|View full text |Cite
|
Sign up to set email alerts
|

Discharge against medical advice: How often do we intervene?

Abstract: BACKGROUND: Discharges against medical advice (AMA) occur in 1% to 2% of hospital stays and are associated with increased morbidity, readmission rates, and 30-day mortality. Risk factors associated with AMA have been investigated, but interventions at the time of discharge have not been carefully examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
(46 reference statements)
0
29
0
Order By: Relevance
“…These visit factors were reviewed because the literature has identified them as being important markers for AMA discharge safety. 6,8 Two research assistants, under the guidance of Dr. Stearns, reviewed the charts. To ensure agreement across chart reviews with respect to subjective questions (eg, whether capacity was adequately documented), the group reviewed the first 10 consecutive charts together; there was full agreement on how to classify the data of interest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These visit factors were reviewed because the literature has identified them as being important markers for AMA discharge safety. 6,8 Two research assistants, under the guidance of Dr. Stearns, reviewed the charts. To ensure agreement across chart reviews with respect to subjective questions (eg, whether capacity was adequately documented), the group reviewed the first 10 consecutive charts together; there was full agreement on how to classify the data of interest.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13][14] Patients with mental illnesses and addiction issues are overrepresented in AMA discharges, and complicated capacity assessments and limited resources may strain providers. 7,8,15,16 Studies have repeatedly shown higher rates of readmission and mortality for AMA patients than for conventionally discharged patients. [17][18][19][20][21] Whether AMA discharge is a marker for other prognostic factors that bode poorly for patients or contributes to negative outcomes, data suggest this group of patients is vulnerable, having mortality rates up to 40% higher 1 year after discharge, relative to conventionally discharged patients.…”
mentioning
confidence: 99%
“…Discharge against medical advice impedes the ability of the healthcare team to provide timely care to the patient . Patients who leave the hospital with an informed refusal of inpatient care do not receive the same discharge care as patients discharged in a standard manner, with fewer DAMA patients receiving discharge plans, outpatient follow-up appointments and necessary prescriptions 21. Since patients who tend to leave against medical advice are less likely to have a primary doctor in the first place,22 there are greater potential negative consequences to them leaving without a discharge plan and follow-up.…”
Section: Rethinking Discharge Against Medical Advice As a Healthcare mentioning
confidence: 99%
“…Patients who leave against medical advice represent a public health and financial concern. They are at increased risk of mortality, morbidity, and readmission and are likely to consume a disproportionate share of increasingly scarce healthcare resources [4,11,13,18,40,44].…”
Section: Introductionmentioning
confidence: 99%